2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-2.13093
|View full text |Cite
|
Sign up to set email alerts
|

Prepuberal stress and obesity: effects on serum corticosterone, prolactin, testosterone and precancerous prostate lesions in adult rats

Abstract: Summary. Stress during puberty and obesity can represent conditions that facilitate the long-term development of diseases, especially for stress-related disorders that depend on neuroendocrine and immune responses. The prostate is prone to diseases that result from neuroendocrine or immune challenges, such as cancer. Aim: In the present study, we assessed the long-term effects of an acute pubertal stressor (immune-challenge) or obesity on the development of precancerous lesions in rats. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
7

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
2
0
7
Order By: Relevance
“…Stress also has negative effects on organs, such as adrenal enlargement and atrophy of the thymus gland, and causes the disruption of homeostasis and dysfunction of the endocrine system and immune cells [ 12 , 13 ]. Herrera-Covarrubias et al [ 14 ] and Araujo et al [ 15 ] also reported stress-induced effects on hormones, suggesting the involvement of stress in hormone function. Furthermore, Kuhn CM et al [ 16 ] reported the effects of stress on growth and immune function, suggesting a reduction in metabolic levels of energy production and cellular response to growth hormones owing to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Stress also has negative effects on organs, such as adrenal enlargement and atrophy of the thymus gland, and causes the disruption of homeostasis and dysfunction of the endocrine system and immune cells [ 12 , 13 ]. Herrera-Covarrubias et al [ 14 ] and Araujo et al [ 15 ] also reported stress-induced effects on hormones, suggesting the involvement of stress in hormone function. Furthermore, Kuhn CM et al [ 16 ] reported the effects of stress on growth and immune function, suggesting a reduction in metabolic levels of energy production and cellular response to growth hormones owing to stress.…”
Section: Introductionmentioning
confidence: 99%
“…28,33,34 Previamente se reportó que la misma dosis de LPS (1.5 mg/kg) en el DPN 35 resultaba en displasia severa de la próstata en el DPN 112 (16 semanas de edad). 24 En el presente trabajo se evaluó la próstata en el DPN 90 (semana 13), corroborando la presencia de lesiones, aunque aparentemente de menor intensidad (displasia leve). Esta evidencia sugiere que la aparición de lesiones es incipiente y van en aumento paulatino, explicando así porqué el estrés y la edad son factores de riesgo para la incidencia del CaP.…”
Section: Discussionunclassified
“…Para confirmar que el LPS tuviera efectos, las ratas se monitorearon a las 2, 4, 8, 24 y 48 h después de la inyección y se evaluó su estado general de respuesta considerando 5 signos de enfermedad (ptosis, piloerección, letargia, acurrucamiento, cifosis) igual a trabajos previos. 24,26,28 En cada evaluación las ratas recibieron un puntaje de 0 a 5, dependiendo del número de signos observados (Figura 1).…”
Section: Grupos Y Tratamientosunclassified
See 2 more Smart Citations